Development of a Structural Model for Breast Cancer Information Dissemination Among Sri Lankan Undergraduates - Manatunga, P.K.S.; Kuruppu, D.C. (Archives of Breast Cancer, 2025)
Background: Breast cancer is a leading public health concern in Sri Lanka, and access to reliable information is essential for early detection. Nonmedical female undergraduates, especially those in the social sciences, often engage in community education. Although this is not an official policy, their potential to raise awareness makes it important to understand how they handle information. This study aimed to develop a statistically validated structural model for the effective dissemination of breast cancer–related information, focusing on 6 constructs: Information Need, Satisfaction, Impact, Information Source, Information Dissemination, and Medium of Information. Methods: A cross-sectional quantitative design was adopted, collecting data from 5 selected state universities using stratified self-weighting random sampling guided by the Krejcie and Morgan table. Data were collected using a structured, validated questionnaire (Cronbach α = 0.876) administered via Google Forms. Analysis was conducted using SPSS version 23 and SmartPLS 3.2.6. Partial least squares structural equation modeling (PLS-SEM) was used to assess the measurement and structural models, focusing on validity, reliability, and model fit. Results: The model initially included 38 indicators, later refined to 33. Bootstrapped analysis (5000 resamples) confirmed 9 of 11 hypotheses; the moderating effects of the Medium of Information were not significant. Conclusion: The findings revealed that Satisfaction significantly contributed to the perceived Impact, while Information Need and Dissemination showed no direct effect. The validated model provides a foundation for designing culturally relevant, evidence-based awareness programs grounded in reliable information Sources tailored to Sri Lankan undergraduates.
Keywords: information seeking behavior; health knowledge-attitudes practice; information dissemination; breast cancer awareness; Sri Lanka